2007
DOI: 10.1080/14786410701256358
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive components in rice husk against mutagens-induced SOS response usingSalmonella typhimuriumTA1535/pSK1002umutest

Abstract: The EtOAc extract from rice (Oriza sativa cv. Hinohikari) husk showed a suppressive effect on umu gene expression of the SOS response in Salmonella typhimurium TA1535/pSK1002 against the mutagen, Trp-P-1, which requires liver metabolizing enzyme. To obtain the suppressive compound, the EtOAc extract was fractionated by SiO(2) column chromatography using umu test as a bioassay guide. Suppressive compound was isolated and identified as momilactone A (1) by EIMS, IR, (1)H- and (13)C-NMR spectroscopy. Compound 1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…According to Mckim [24], a methanol extract of japonica rice husk ( MEJRH) inhibited human colon cancer cell proliferation in dimethylhydrazine-induced rats. Okuno and Miyazawa [25] reported that momilactone-A from an ethyl acetate extract of rice husk ( AERH) suppressed the SOS-inducing activity of Trp-P-1 in the Salmonella antimicrobial usage ( Amu) test. A dichloromethane extract of purple rice husk strongly inhibited aflatoxin B1 ( AFB1) and MeIQ-( amino-imidazo-quinolines denoted IQ compounds), induced mutagenesis in the Ames test and decreased the number of micronuclei in the liver of diethylnitrosamine-induced rats [20].…”
Section: Introductionmentioning
confidence: 99%
“…According to Mckim [24], a methanol extract of japonica rice husk ( MEJRH) inhibited human colon cancer cell proliferation in dimethylhydrazine-induced rats. Okuno and Miyazawa [25] reported that momilactone-A from an ethyl acetate extract of rice husk ( AERH) suppressed the SOS-inducing activity of Trp-P-1 in the Salmonella antimicrobial usage ( Amu) test. A dichloromethane extract of purple rice husk strongly inhibited aflatoxin B1 ( AFB1) and MeIQ-( amino-imidazo-quinolines denoted IQ compounds), induced mutagenesis in the Ames test and decreased the number of micronuclei in the liver of diethylnitrosamine-induced rats [20].…”
Section: Introductionmentioning
confidence: 99%